Proses Translasi Representasi dalam Memahami Teorema Pythagoras Ditinjau dari Gaya Belajar Mahasiswa - Muhammad Zuhhad Achyar; Nugraha, Yandika; Syawahid, M. (STAI Darul Kamal Darul Kamal NW Kembang Kerang, 2025)
This study aims to describe the translation of representation in understanding the Pythagorean theorem in terms of students' learning styles. Representation has an important role in learning mathematics. Representation as a means of understanding concepts and mathematical thinking and revealing conceptual understanding. The research method uses a qualitative approach. The subjects of this study came from 85 mathematics education students from the State Islamic University of Mataram. The selection of subjects was based on the results of a learning style questionnaire with categories of visual learning style, auditory learning style, and kinesthetic learning style. Data collection techniques used a learning style questionnaire, a Pythagorean theorem test instrument and task-based interviews. This study has proven that students successfully completed the Pythagorean theorem problems because they were able to carry out the translation process from verbal to visual representation and from visual to symbolic. This indicates that understanding concepts and the ability to change information in various forms of representation greatly influence success in solving mathematical problems.